Preparation method and application of mesoporous scale flower-shaped carbonaceous adsorbent rich in carbon

CN118719021BActive Publication Date: 2026-10-16XIANGTAN UNIV
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411002116.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-07-25
Publication Date
2026-10-16
Estimated Expiration
2044-07-25

AI Technical Summary

Technical Problem

现有技术中未经活化或改性处理的多孔炭质吸附剂一般都存在吸附位点少、扩散速率慢、染料吸附容量低、吸附剂回收利用困难等问题

Benefits of technology

1).本发明以无氧富氮的六次甲基四胺为有机配体与钴金属配位,在葡萄糖交联剂作用下自组装形成富氮配体的金属有机骨架,两步热解得到富含介孔尺度且具有花状形貌的氮掺杂多孔炭质吸附剂,金属有机骨架发挥了碳源和模板剂的双效作用,避免使用其他模板剂;

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118719021B_ABST
    Figure CN118719021B_ABST
Patent Text Reader

Abstract

The application discloses a preparation method and application of a mesoporous scale flower-shaped carbonaceous adsorbent. The method comprises the following steps: one-pot hydrothermal reaction of glucose, soluble cobalt salt and hexamethylenetetramine in an aqueous solution, centrifugal filtration and drying of solid matters after the reaction to obtain a precursor; low-temperature carbonization of the precursor in an inert atmosphere to obtain a pre-carbonized product; further high-temperature carbonization treatment of the pre-carbonized product in an inert atmosphere, removal of soluble cobalt species through acid pickling, deionized water washing and drying to obtain the mesoporous scale flower-shaped carbonaceous adsorbent. The mesoporous scale of the adsorbent is mainly located in the range of 3-10 nm. Compared with a traditional method, the preparation method is simple and easy to implement, has low cost, does not need to use a template reagent, can be prepared in a large amount, the flower-shaped carbonaceous adsorbent has high specific surface area, rich mesoporous structure and stable size, is beneficial to a mass transfer process, and has excellent adsorption and purification effects when treating dyes in water.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of wastewater treatment adsorption materials technology, specifically to a method for preparing a mesoporous, flower-like carbonaceous adsorbent and its dye adsorption application. Background Technology

[0002] The textile printing and dyeing industry, paper mills and pulp mills, and paint and tanneries are major sources of dye wastewater. Direct discharge of untreated dye wastewater into water bodies causes serious pollution to the aquatic ecosystem. In particular, most dye molecules are highly toxic and biodegradable. Trace amounts of dye in water severely affect light transmittance, posing a significant threat to the growth environment of aquatic organisms. Furthermore, dyes can be transmitted to humans through the food chain, adversely affecting both the ecological environment and human health.

[0003] Dye removal methods mainly include physical methods, chemical methods, biodegradation, and advanced oxidative degradation. Among these, adsorption, a physical method, is simple to operate and has extremely high decolorization efficiency for various dyes. In particular, adsorption does not produce harmful sludge or other harmful intermediates, making it considered the most practical wastewater treatment method. Carbon-based porous materials have high stability, high porosity, and large adsorption capacity; however, the high specific surface area of ​​activated carbon, the most commonly used material, requires large amounts of corrosive activating reagents, involves multiple reaction steps, is costly, and has poor regenerability, severely limiting its large-scale application. The key to dye removal by adsorption lies in finding an adsorbent that is simple to prepare, low in cost, has excellent removal effect, and good regenerability. Hierarchical porous carbon materials with controllable morphology and texture properties have attracted widespread interest, as their hierarchical structure can promote rapid dye diffusion within the pores of the adsorbent. Studies have shown that porous carbon materials with tubular, blocky, rhomboid, spherical, and flower-like morphologies possess abundant active sites that can anchor dye molecules, making them ideal structures for rapid dye diffusion. Flower-like porous carbon materials, in particular, have attracted researchers' attention due to their unique shape and rich pore characteristics. The literature (Carbon, 2020, 161: 97-107) reports a mesoporous flower-like porous carbon material formed by polymer pyrolysis using a soft template. Hard templates are also a common method for preparing flower-like porous carbon; the literature (J. Mater. Chem. A, 2017, 5: 6245) reports a mesoporous flower-like carbon material obtained through a glucose precursor template process. Patent CN104891491B discloses a method for preparing tubular activated carbon based on bamboo shoot shells, obtaining a tubular microporous carbon material through high-concentration KOH activation treatment and acid washing. Admittedly, hierarchical porous carbon materials with specific morphologies are mainly obtained through polymer or template methods. These processes involve the use of large amounts of toxic organic reagents and etching to remove the template, making the preparation process complex and difficult to scale up for industrial production. Therefore, the directional and controllable synthesis of hierarchical porous carbon materials with specific structures remains a pressing issue.

[0004] Compared to activated carbon and polymer-derived porous carbon materials, metal-organic frameworks (MOFs) have significant advantages in dye adsorption due to their rich pore structure and good metal coordination effect. The organic ligands in the MOF structure can also directly serve as carbon sources to transform into porous carbon materials, achieving morphological replication in derived porous carbon materials without the need for template removal. However, obtaining nitrogen-doped flower-like carbon materials with high mesoporosity remains a significant challenge. Existing porous carbon adsorbents without activation or modification generally suffer from problems such as few adsorption sites, slow diffusion rates, low dye adsorption capacity, and difficulties in adsorbent recovery. Therefore, developing a simple process to obtain hierarchical porous carbon adsorbents with both excellent dye adsorption capacity and good separation and recovery capabilities is of great importance. This invention utilizes oxygen-free, nitrogen-rich hexamethylenetetramine as a linker to coordinate with cobalt metal, forming a nitrogen-rich ligand MOF under the action of a glucose crosslinking agent. The MOF was subjected to two pyrolysis processes and acid washing under an inert atmosphere to obtain a nitrogen-doped flower-like carbonaceous adsorbent rich in mesoporous structures. The mesoporous structure can act as a fast channel for dye molecules, and trace cobalt species in the adsorbent can form a stable Co-N group with nitrogen. x The active site structure enables the adsorbent to have a high adsorption capacity for cationic dyes (adsorption capacities of 400.1 mg / g for malachite green and 284 mg / g for rhodamine B), while also exhibiting rapid adsorption efficiency, achieving purification within approximately 2 hours. Summary of the Invention

[0005] To overcome the difficulties mentioned in the background art, the present invention aims to provide a method for preparing a mesoporous nitrogen-doped flower-like carbonaceous adsorbent with simple preparation process, high yield, stable structure, and high adsorption efficiency for dyes. The adsorbent has a distinct nano-flower-like structure and contains trace amounts of cobalt, exhibiting high mesoporosity and magnetism, and demonstrates high adsorption efficiency for cationic dyes.

[0006] This invention is implemented by the following method: This invention first provides a method for preparing a nitrogen-doped flower-like carbonaceous adsorbent rich in mesoporous scale, comprising the following steps: (1) Preparation of the precursor: Glucose, soluble cobalt salt and hexamethylenetetramine are dissolved in deionized water and then placed in a reaction vessel lined with polytetrafluoroethylene for hydrothermal reaction. After the reaction is completed, the solid is centrifuged, filtered and dried to obtain the precursor. (2) Pre-carbonization treatment, specifically: the precursor is carbonized at low temperature in an inert atmosphere in a tube furnace to obtain a cobalt-containing pre-carbide; (3) Carbonization reaction, specifically: the pre-carbonized material is further carbonized under an inert atmosphere, and after the reaction is completed, it is cooled to room temperature, and then the soluble cobalt species are removed by acid washing, washed with deionized water and dried to obtain the adsorbent.

[0007] In the preferred embodiment of the above technical solution, during the preparation of the precursor, the soluble cobalt salt is at least one of cobalt nitrate, cobalt sulfate, cobalt acetate, and cobalt chloride; the mass ratio of glucose to cobalt salt is 1:1 to 10, and the mass molar ratio of cobalt salt to hexamethylenetetramine is 1:1 to 6; the hydrothermal reaction temperature is 140 to 200 °C, and the hydrothermal reaction time is 6 to 24 h.

[0008] In the preferred embodiment of the above technical solution, the pre-carbonization reaction temperature of the precursor is 350–500℃, the carbonization time is 0.5–4 h, and the heating rate is 2–6℃ / minh.

[0009] In the preferred embodiment of the above technical solution, the further carbonization reaction temperature of the pre-carbonized material is 600–900℃, the heating rate is 1–10℃ / min, and the carbonization reaction time is 0.5–4 h.

[0010] The application technology of this invention is characterized by the application of a mesoporous nitrogen-doped flower-shaped carbonaceous adsorbent in the adsorption treatment of dye wastewater. The specific method is as follows: the adsorbent is added to an aqueous solution containing dye, and the mixture is stirred at a constant temperature until adsorption equilibrium is reached, thus completing the dye adsorption.

[0011] In a specific embodiment, in the method, the pH of the dye aqueous solution is 2-10, the solution temperature is 0-40℃, and the mass ratio of adsorbent to dye in the solution is (0.01-1):1; the dye includes at least one of Congo red, rhodamine B, methylene blue, malachite green, and crystal violet.

[0012] In a specific embodiment, the method involves stirring the dye aqueous solution for 1 to 360 minutes after adding the adsorbent, centrifuging to separate the adsorbent, and then performing absorbance scanning analysis on the solution.

[0013] Compared with the prior art, the beneficial effects of the present invention include: 1) This invention uses oxygen-free, nitrogen-rich hexamethylenetetramine as an organic ligand to coordinate with cobalt metal. Under the action of glucose crosslinking agent, it self-assembles to form a nitrogen-rich metal-organic framework. Two-step pyrolysis yields a nitrogen-doped porous carbon adsorbent rich in mesopores and with a flower-like morphology. The metal-organic framework plays a dual role as a carbon source and template agent, avoiding the use of other template agents. 2) The adsorbent provided by this invention has a moderate specific surface area but abundant mesopore size, with pore size ranging from 3 to 10 nm, which is very suitable for the rapid diffusion of dye molecules. In particular, it has a specific adsorption capacity for malachite green dye, and the adsorption capacity is greater than that of other types of unactivated carbon adsorbents. 3) The adsorbent provided by this invention contains trace amounts of cobalt, which makes it magnetic. Magnetic separation can be used in the later stages of application to achieve rapid, efficient, and low-cost recovery of the adsorbent, which has great application prospects in the field of water treatment. Attached Figure Description Figure 1 This is a transmission electron microscope (TEM) image of the carbonaceous adsorbent described in Example 1; Figure 2 The nitrogen adsorption isotherm and pore size distribution diagram of the carbonaceous adsorbent described in Example 1 are shown below. Figure 3 The kinetic curves of malachite green adsorption by the carbonaceous adsorbent described in Example 1 at different temperatures are shown. Figure 4 The cyclic adsorption performance of the carbonaceous adsorbent for malachite green dye described in Example 1; Figure 5 This is a diagram illustrating the magnetic recovery effect of the carbonaceous adsorbent described in Example 1. Figure 6 The nitrogen adsorption isotherm and pore size distribution of the carbonaceous adsorbent described in Example 2 are shown for comparison. Detailed Implementation

[0014] The present invention will now be described through specific embodiments. It should be noted that the embodiments described herein are merely illustrative of the invention and are not intended to limit the scope of the invention. Those skilled in the art can implement the invention using various combinations of the claims.

[0015] Example 1: A method for preparing a nitrogen-doped flower-like carbonaceous adsorbent rich in mesoporous scale includes the following steps: (1) Preparation of precursor: Weigh 2g glucose, 2g cobalt nitrate hexahydrate and 4g hexamethylenetetramine and stir thoroughly to dissolve in 60mL deionized water. Place the solution in a polytetrafluoroethylene-lined reactor and react at 180℃ for 10h. After cooling to room temperature, centrifuge to separate the solid product, wash and dry to obtain the metal-organic framework precursor. (2) Pre-carbonization treatment, specifically: weigh 1g of metal-organic framework precursor and place it in a tube furnace under nitrogen atmosphere at 450°C for 2h constant temperature carbonization treatment, with a heating rate of 4°C / min, to obtain cobalt-containing pre-carbide. (3) Carbonization reaction, specifically: the cobalt-containing precarbide is further carbonized at 900°C for 2 hours under nitrogen atmosphere with a heating rate of 4°C / min. After the reaction, the carbide is refluxed in 1 mol / L hydrochloric acid solution at 60°C for 2 hours to remove soluble cobalt species. Then it is washed with deionized water until neutral and dried overnight to obtain a mesoporous flower-like carbon adsorbent, labeled as GNC-900.

[0016] The application of the mesoporous flower-like carbonaceous adsorbent (GNC-900) obtained in this embodiment in dye adsorption, the adsorbent structure and application performance are described in [link to relevant documentation]. Figures 1-5 The maximum adsorption capacity of different dyes in the adsorbent is shown in Table 1, and the specific steps include the following: 1) Weigh 0.02g of the GNC-900 adsorbent and add it to 100 mL of an aqueous solution containing malachite green dye. The concentration of malachite green in the aqueous solution is 350 mg / L. Stir the mixture thoroughly for 6 h under magnetic stirring. Take 1 mL of the mixture every 5 min with a pipette, centrifuge and filter it, and then measure the absorbance of the supernatant at a specific wavelength using a UV-Vis spectrophotometer.

[0017] 2) After adsorption is complete, the adsorbent remaining after dye adsorption can be easily obtained using magnetic separation. Figure 5 The adsorbent was recovered by washing three times with anhydrous ethanol, centrifuging, and drying overnight. The dried adsorbent could then be used for a second cycle performance test of the dye.

[0018] The adsorbent's adsorption application in other dyes is similar to that of malachite green. Measurement results show that the maximum adsorption capacities of the adsorbent GNC-900 for several cationic dyes, including malachite green, rhodamine B, methylene blue, and crystal violet, are 400.1 mg / g, 284 mg / g, 234 mg / g, and 281 mg / g, respectively.

[0019] Depend on Figure 1 It can be seen that: From Figure 1 The transmission electron microscope shows that the GNC-900 adsorbent has a distinct flower-like morphology. This is because cobalt metal and organic ligands form an amorphous carbon layer-encapsulated metal-organic framework under the action of glucose crosslinking agent. During high-temperature pyrolysis, the glucose crosslinking agent undergoes thermal condensation and polycondensation, forming a flower-like morphology on the outer surface of the adsorbent.

[0020] Depend on Figure 2 It can be seen that the nitrogen adsorption-desorption isotherm of the adsorbent has a significant hysteresis loop at a relative pressure of 0.45, confirming that it has abundant mesoporous scale structure. Figure 2 The pore size distribution curves in the data confirm that the mesopore size of the adsorbent is mainly located in the range of 3–10 nm, a size that is very suitable for the diffusion of dye molecules.

[0021] Depend on Figure 3 It can be seen that the adsorption of malachite green in the solution is affected by temperature. The amount of adsorption increases with increasing temperature, but the increase gradually decreases, indicating that the adsorption of malachite green by the adsorbent is chemical adsorption. The adsorption diffusion rate of the dye in the adsorbent is relatively fast, and the adsorption equilibrium is basically achieved within 120 min. This is because: (1) The large number of wide-sized mesopores in the adsorbent are conducive to the diffusion of dye molecules. The higher the temperature, the faster the diffusion rate of dye molecules, and the shorter the equilibrium time required for dye molecules in the adsorbent. The adsorption equilibrium time at 40℃ is only 10 min; (2) Co-N in the adsorbent x The active sites can react chemically with the dye to form coordination bonds, thereby increasing the amount of dye adsorbed when the solution temperature rises; (2) The increase in temperature will also lead to an increase in the solubility of the dye in water and a decrease in the interaction force between the dye molecules and the adsorbent. Therefore, the trend of increasing temperature and the trend of increasing adsorption amount are not proportional.

[0022] Depend on Figure 4 It can be seen that the adsorbent has good recycling performance, and the removal rate of malachite green dye is still higher than 65% after 5 adsorption treatments. Figure 5 The adsorbent, after adsorbing the dye, can be efficiently recovered using magnetic analysis. The adsorption process is low-cost and has excellent prospects for industrial application. Example

[0023] Example 2 differs from Example 1 in that the reaction temperature for further carbonization of the pre-carbide is different; specifically, in this example, the pre-carbide is treated at a constant temperature of 800°C for 2 hours under a nitrogen atmosphere. The process includes the following steps: (1) Preparation of precursor: Weigh 2g glucose, 2g cobalt nitrate hexahydrate and 4g hexamethylenetetramine and stir thoroughly to dissolve in 60mL deionized water. Place the solution in a polytetrafluoroethylene-lined reactor and react at 180℃ for 10h. After cooling to room temperature, centrifuge to separate the solid product, wash and dry to obtain the metal-organic framework precursor. (2) Pre-carbonization treatment, specifically: weigh 1g of metal-organic framework precursor and place it in a tube furnace under nitrogen atmosphere at 450°C for 2h constant temperature carbonization treatment, with a heating rate of 4°C / min, to obtain cobalt-containing pre-carbide. (3) Carbonization reaction, specifically: the cobalt-containing precarbide is further carbonized at 800°C for 2 hours under nitrogen atmosphere with a heating rate of 4°C / min. After the reaction, the carbide is refluxed in 1 mol / L hydrochloric acid solution at 60°C for 2 hours to remove soluble cobalt species. Then it is washed with deionized water until neutral and dried overnight to obtain a mesoporous flower-like carbon adsorbent. Example

[0024] Example 3 differs from Example 1 in that the reaction temperature for pre-carbonization of the metal-organic framework precursor to form the precarbide is different; specifically, the metal-organic framework precursor is pre-carbonized at 550°C for 2 hours under a nitrogen atmosphere to form the precarbide. The process includes the following steps: (1) Preparation of precursor: Weigh 2g glucose, 2g cobalt nitrate hexahydrate and 4g hexamethylenetetramine and stir thoroughly to dissolve in 60mL deionized water. Place the solution in a polytetrafluoroethylene-lined reactor and react at 180℃ for 10h. After cooling to room temperature, centrifuge to separate the solid product, wash and dry to obtain the metal-organic framework precursor. (2) Pre-carbonization treatment, specifically: weigh 1g of metal-organic framework precursor and place it in a tube furnace under nitrogen atmosphere at 550°C for 2h constant temperature carbonization treatment, with a heating rate of 4°C / min, to obtain cobalt-containing pre-carbide. (3) Carbonization reaction, specifically: the cobalt-containing precarbide is further carbonized at 900°C for 2 hours under nitrogen atmosphere with a heating rate of 4°C / min. After the reaction, the carbide is refluxed in 1 mol / L hydrochloric acid solution at 60°C for 2 hours to remove soluble cobalt species. Then it is washed with deionized water until neutral and dried overnight to obtain a mesoporous flower-like carbon adsorbent. Example

[0025] Example 4 differs from Example 1 in that the reaction temperature for the one-pot hydrothermal reaction to form the metal-organic framework precursor is different; specifically, the metal-organic framework precursor is formed under hydrothermal reaction conditions at 160°C. The process includes the following steps: (1) Preparation of precursor: Weigh 2g glucose, 2g cobalt nitrate hexahydrate and 4g hexamethylenetetramine and stir thoroughly to dissolve in 60mL deionized water. Place the solution in a polytetrafluoroethylene-lined reactor and react at 160℃ for 10h. After cooling to room temperature, centrifuge to separate the solid product, wash and dry to obtain the metal-organic framework precursor. (2) Pre-carbonization treatment, specifically: weigh 1g of metal-organic framework precursor and place it in a tube furnace under nitrogen atmosphere at 450°C for 2h constant temperature carbonization treatment, with a heating rate of 4°C / min, to obtain cobalt-containing pre-carbide. (3) Carbonization reaction, specifically: the cobalt-containing precarbide is further carbonized at 900°C for 2 hours under nitrogen atmosphere with a heating rate of 4°C / min. After the reaction, the carbide is refluxed in 1 mol / L hydrochloric acid solution at 60°C for 2 hours to remove soluble cobalt species. Then it is washed with deionized water until neutral and dried overnight to obtain a mesoporous flower-like carbon adsorbent.

[0026] The mesoporous, flower-like carbonaceous adsorbents obtained in Examples 2-4 can all be used for dye adsorption, and their specific properties are shown in Table 1. Compared with Example 1, although they have a relatively smaller specific surface area, the adsorbents also contain abundant Co-N... x Its active sites and mesoporous size enable it to have a fast adsorption rate for several different cationic dyes, such as Rhodamine B, methylene blue, malachite green, and crystal violet. In particular, its adsorption capacity for malachite green is as high as 330 mg / g, which is far greater than that of similar unactivated or unmodified carbon adsorbents. Even after five cycles of use, the adsorption removal rate is still over 70%.

[0027]

[0028] Comparative Example 1: The difference from Example 1 is that the metal-organic framework precursor was directly carbonized in one step under a nitrogen atmosphere to obtain the adsorbent. Specifically, 1g of dried metal-organic framework precursor was weighed and placed in a tube furnace for constant temperature treatment at 900°C for 2 hours under a nitrogen atmosphere. The resulting sample was labeled DNC-900.

[0029] Comparative Example 2: The difference from Example 1 is that only glucose and soluble cobalt nitrate were used as raw materials in the hydrothermal reaction, and the precursor was formed by a low-temperature hydrothermal reaction. Specifically: Weigh out 2 g of glucose and 2 g of cobalt nitrate hexahydrate and stir to dissolve in 60 mL of deionized water. React at 180 °C for 10 h in a sealed polytetrafluoroethylene-lined reactor. After cooling to room temperature, centrifuge to separate the solid product, wash and dry to obtain the precursor. 1g of dried precursor was weighed and placed in a tube furnace under nitrogen atmosphere at 450°C for 2h, with a heating rate of 4°C / min, to obtain pre-carbonized material. The pre-carbonized material was further carbonized at 900°C for 2 hours under a nitrogen atmosphere with a heating rate of 4°C / min. After the reaction was completed, the carbide was refluxed in 1 mol / L hydrochloric acid solution at 60°C for 2 hours to remove soluble cobalt species. It was then washed with deionized water until neutral and dried overnight to obtain the adsorbent.

[0030] The adsorbents obtained in Comparative Examples 1 and 2 are applied to dye adsorption. The method is the same as in Example 1, specifically including the following steps: 1) Weigh 0.02g of the adsorbent from Comparative Examples 1-2 and add it to 100 mL of an aqueous solution containing malachite green dye. The concentration of malachite green in the aqueous solution is 350 mg / L. The mixture is stirred thoroughly for 6 h under magnetic stirring. Every 5 min, 1 mL of the mixture is taken out by pipette, centrifuged and filtered, and the absorbance of the supernatant is measured at a specific wavelength using a UV-Vis spectrophotometer.

[0031] 2) After adsorption, the adsorbent after dye adsorption can be easily obtained by magnetic separation. It is then washed three times with anhydrous ethanol, collected by centrifugation, and dried overnight to achieve adsorbent recovery. The dried adsorbent can then be directly used for a second cycle performance test of the dye.

[0032] Compared to Examples 1 and 2, the adsorbents described in Examples 1 and 2 exhibited significantly longer equilibrium times and lower adsorption capacities under the same conditions. For instance, in Example 2, the adsorbent GC-900 required 360 minutes to reach equilibrium for malachite green dye. This is because the pore structure of the adsorbent in Example 2 was primarily composed of micropores. The nitrogen adsorption isotherm and pore size distribution diagram are shown below. Figure 5 Although the adsorbent described in Comparative Example 2 has a specific surface area as high as 611 m². 2 / g, but the pore size is mainly below 2 nm, which is not suitable for the diffusion of dye molecules. These comparative examples fully demonstrate that the determining factor for dye adsorption is not the specific surface area of ​​the adsorbent, but the mesoporous structure and active sites of a specific size in the adsorbent.

[0033] The above description is merely a preferred embodiment of the present invention and is not intended to limit the invention. Various modifications and variations can be made to the present invention by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.

Claims

1. A method for preparing a mesoporous, flower-like carbonaceous adsorbent, characterized in that, It consists of the following steps: (1) Preparation of the precursor: Glucose, soluble cobalt salt and hexamethylenetetramine are dissolved in deionized water and then placed in a polytetrafluoroethylene-lined reactor for hydrothermal reaction. After the reaction is completed, the solid is centrifuged, filtered and dried to obtain the precursor. The hydrothermal reaction temperature is 160-180 °C and the hydrothermal reaction time is 6-24 h. The soluble cobalt salt is at least one of cobalt nitrate, cobalt sulfate, cobalt acetate and cobalt chloride. The mass ratio of glucose to cobalt salt is 1:1-10 and the molar ratio of cobalt salt to hexamethylenetetramine is 1:1-6. (2) Pre-carbonization treatment, specifically: the precursor is carbonized at low temperature in an inert atmosphere in a tube furnace to obtain a cobalt-containing precarbide; the low temperature carbonization temperature is 350-500 °C and the reaction time is 0.5-4 h; (3) Carbonization reaction, specifically: the pre-carbonized material is further carbonized under an inert atmosphere, cooled to room temperature after the reaction is completed, and then the soluble cobalt species are removed by acid washing, washed with deionized water and dried to obtain the adsorbent; the carbonization temperature is 900 ℃, the heating rate is 1~10 ℃ / min, and the carbonization reaction time is 0.5~4 h.

2. The application of the mesoporous flower-like carbonaceous adsorbent prepared by the method according to claim 1 in dye adsorption, characterized in that, The aqueous solution containing the dye has a pH of 2 to 10 and a solution temperature of 0 to 40 °C. The mass ratio of adsorbent to dye in the solution is (0.01 to 1):

1. The dye includes at least one of Rhodamine B, methylene blue, malachite green, and crystal violet.

3. The application according to claim 2, characterized in that, The adsorbent after dye adsorption is recovered and reused through a simple magnetic action; after recovering the adsorbent after dye adsorption, the adsorbent is also recycled. The adsorbent is rinsed with any one of deionized water, dilute hydrochloric acid, methanol, ethanol and NaOH, and after centrifugation, filtration and drying of the adsorbent, the recycling performance test of the adsorbent is carried out according to the application conditions described in claim 2.

Citation Information

Patent Citations

  • A kind of preparation method of bamboo shoot shell-based activated carbon for supercapacitor

    CN104891491B

  • Porous magnetic carbon material as well as preparation method and application thereof

    CN115974048A

  • Magnetic derivative cobalt nitrogen doped carbon adsorption material and preparation method and application thereof

    CN116747845A

  • Preparation method of non-noble metal supported carbon catalyst and application of non-noble metal supported carbon catalyst in preparation of furfuryl alcohol through furfural hydrogenation

    CN117181225A